Assessing factors influencing the uptake of the health insurance subsidy program: a case of Turkana Central Sub county in Kenya - Lolos, Nelson Lodiita (Strathmore University, 2018)
The attainment of universal health coverage is a top global priority as advanced by WHO and member countries, including Kenya. Social health insurance schemes, like the Health Insurance Subsidy for the Poor serve as one of the means to achieve the UHC challenges of access to care, equity and affordability of services.The purpose of this study was to assess effectiveness of such SHI programmes in improving satisfaction, access and utilization of healthcare among the beneficiaries in Turkana central sub-County. The target respondents were beneficiaries of this programme (household heads), managers of implementing programme (NHIF, County health department, social services and children’s departments). This was a descriptive, cross-sectional case study that used mixed (both qualitative and quantitative) methodology for data collection. The sample size was 140 respondents randomly selected from the sampling frame while the key informants were purposively selected. Semi-structured questionnaire, focus group discussion (FGD) and in-depth interview (IDI) guides were used to collect data. STATA (version 15) statistical software was used to analyse the quantitative data. Qualitative data from IDIs and FGDs were coded and categorized into profiles, themes, topics or incidents as appropriate. Content analysis was done using conceptual approaches including grounded theory approach and framework approach. The findings indicate that the utilization rate of health facilities was at 0.3 visits per capita per year. Only about 18% of household members reported illness in the preceding 4 weeks, and of those, 83% sought care from health facilities. The most accessed service was outpatient. About 54% of members of households reported being sick in the preceding 4 weeks but did not seek care. Reasons given for not seeking care included OOP hidden costs, self-medication, long distances to providers, etc. Majority of respondents rated the HISP as good (3.4 points out of 5) but had concerns about quality of care, availability of services and health workers’ attitudes.This study recommends continuous awareness creation, advocacy, communication and social mobilization of beneficiaries. It further recommends that health providers improve quality and availability of services. The study also recommends policy shift on health financing, increase in allocation of resources to health financing and social protection programmes as well as better coordination.
Keywords: Improving satisfaction; SHI programmes; Universal health coverage; Health Insurance Subsidy